The Concept and Characteristics of Quranic Advice in the AI Era: A Tafsir bil-Ma'tsur and Contextualist - Fadhilah, Umi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This research analyzes the Qur'anic concept of "advice" as a fundamental ethical principle and its relevance in the era of Artificial Intelligence (AI). By redefining "advice" from literal guidance to a transformative moral action, the study contrasts traditional ethics with the mechanics of modern AI recommendation systems. Using a qualitative-descriptive method, this research integrates Tafsir bil-Ma'tsūr (via Shafwatut Tafāsīr) and the Wujūh wa Naẓā'ir approach, synthesized through Abdullah Saeed's Contextualist framework and the "Double Movement" theory to bridge historical textual values with contemporary technological challenges. The findings reveal a dualistic character of counsel in the Qur'an: the sincere mandate of the prophets versus manipulative counsel used for deception, such as in the stories of Satan and Joseph's brothers. This proves that "advice" is not ethically neutral but is fundamentally defined by intention and context. Consequently, this study provides a vital theological critique of "algorithmic advice" that is often exploitative in nature. By offering a religious ethical framework based on trust (amanah) and sincerity (ikhlas), this research contributes a normative foundation for AI development that prioritizes human dignity and moral accountability, while providing practical insights into mitigating information manipulation in the digital era.